Intersectional Barriers to Gender Inequality in the Workplace across Race and Disability - Hariadi, Hariadi; Alamsyah, Noor; Yayat, Yayat (Journal Social Civilecial, 2024)
One phenomenon that has for long haunted workplaces is gender inequality despite the new push for diversity and inclusion. This qualitative work looks at how gender as well as other axes of differentiation like race, class, sexual orientation, and/or disability inform, constrain or produce employees’ experiences of inequality in organizational environment. The study explores organisational factors that put up gender-based differences by focusing on structural relativity, cultural expectation, and polity The study is based on 25 participants from different sectors, focus group interviews, and documents analysis. It will be shown that although most companies have diversity and inclusion policies in effect, these may not be effectively being practiced, and/or that there is a lack of policies that respond to the realities of multiply oppressed persons. Some few of the causes of this marginalization include cultural bias particularly from male dominated organizations. Furthermore, this paper reveals that current workplace policies are still lacking especially on subject like parental leave and promotion policies that continue to perpetuate gender stereotypes at the workplace. Finally, it is imperative for future scholarship to continue the important work of Choo and Diversifying Feminisms, insisting on an intersectional approach at the policy and cultural levels for organizations committed to addressing gender inequality in the workplace. Hence, the discovery advances the existing dialogue on workplace disparities and offer the appropriate guidelines for equality approaches across a range of organizations.